The importance of the pelvis and the consequences of its incorrect positioning - Puchalska-Sarna, Anna; Sarna, Michał; Touma, Victor (Technium BioChemMed, 2025)
The pelvic bone consists of three main parts: the ilium (ilium), the ischium (ischium), and the pubis (pubis). The ilium contains a shaft and a plate with characteristic anatomical structures, such as the iliac crest, iliac spines, the auricular surface, and numerous muscle attachments, including the abdominal muscles, gluteal muscles, and thigh muscles. The ischium contains the ischial tuberosity and ischial spine, which are the attachment points for the posterior thigh muscles and ligaments such as the sacrotuberous ligament. The pubic bone contains the pubic crest, the pubic tubercle, and the point of attachment to the other pubic bone via the pubic symphysis. The pelvis, as a whole, consists of the sacrum, the coccyx, and the two pelvic bones, connected by ligaments and membranes such as the sacroiliac ligament, the inguinal ligament, and the obturator membrane. Functionally, the pelvis serves as a bridge between the trunk and the lower limbs and plays a key role in load transfer, postural stabilization, and movement. Changes in pelvic position directly impact the spine, posture, and gait. Pelvic asymmetries can be structural (resulting from anatomical structure) or functional (related to physical activity, lateralization, or medical conditions). The most common types of asymmetry include a pelvic tilt in the frontal plane (e.g., a higher iliac crest) or pelvic rotation in the transverse plane. Such imbalances can lead to uneven weight distribution, overload, back pain, and apparent shortening of the lower limb. They are often accompanied by changes in the position of the spine, shoulders, and head. This asymmetry may be compensatory for scoliosis or a leg length discrepancy. In a lordotic posture, there is excessive anterior pelvic tilt, deepening of the lumbar lordosis, and shortening of the hip flexors (including the iliopsoas muscles) and spinal erectors. The gluteal, abdominal, and hamstring muscles are weakened and stretched. In a flat back posture, there is a flattening of the lumbar lordosis, often with posterior pelvic tilt and shortening of the gluteal and hamstring muscles. A lateral pelvic tilt causes a lift in one of the iliac crests. This results in shortening of the muscles on that side (e.g., the quadratus lumborum) and lengthening of the muscles on the opposite side. This can lead to balance disorders, unequal leg length, postural difficulties, and compensatory spinal curvature. Additionally, a difference in shoulder height and head tilt can occur. The quadratus lumborum plays a key role in stabilizing the lumbar spine, lateral flexion of the trunk, and elevation of the iliac crest. Shortening this muscle limits pelvic and spine mobility, particularly during walking or climbing stairs. The gluteus medius is responsible for thigh abduction and pelvic stabilization in the frontal plane. Its weakness leads to Trendelenburg gait and balance disorders. Dynamic tests such as single-leg stance, squats, lunges, and gait analysis are used to assess functional pelvic asymmetry. Assessment of limb length, range of motion, muscle tone, and possible compensations are also crucial. Manual muscle assessment of the quadratus lumborum, gluteus medius, tensor fascia lata, and adductors is also crucial. Pelvic dysfunction, such as torsion or displacement of the ilium, can affect lower limb length, sacrum alignment, and lumbar spine alignment. Posterior rotation of the right ilium can cause apparent leg shortening, compensatory vertebral rotation, and deep muscle tension (especially in the iliopsoas). Sacral movements, such as nutation and counternutation, are essential for flexibility and load-bearing, and their restriction leads to postural dysfunction. In summary, the pelvis plays a crucial role in maintaining balance, stability, and mobility. Its malalignment affects the entire musculoskeletal system. Therefore, a detailed functional assessment and appropriately selected corrective exercises are essential in the treatment of patients with pelvic asymmetry and disorders.